Synthesis and properties of lead-free BNT-BT-xCZ ceramics as high-temperature dielectrics. (January 2022) - Schulz, Thomas; Veerapandiyan, Vignaswaran; Deluca, Marco; Töpfer, Jörg
Highlights: Bi0.5 Na0.5 TiO3 -based perovskites are potential high temperature capacitor dielectrics. BaTiO3 - and CaZrO3 -modified Bi0.5 Na0.5 TiO3 solid solution exhibits relaxor-like characteristics. synthesis protocol of bismuth-rich perovskites requires precise control of Bi2 O3 raw material. composition with x = 0.2 shows excellent temperature-stable dielectric properties up to 300°C. Abstract: Bulk ceramic samples of the perovskite series (1-x)(0.94Bi0.5 Na0.5 TiO3 -0.06BaTiO3 )-xCaZrO3 with 0 ≤ x ≤ 0.2 were prepared using the conventional solid-state route. It is shown that careful characterization of Bi2 O3 raw materials is essential to avoid deviations from the nominal composition. X-ray diffraction analysis reveals formation of perovskite main phase, and a relaxor-like response of the relative permittivity over temperature was observed. Flattening of the permittivity-temperature curves is observed with increasing CaZrO3 fraction, while maintaining low dielectric losses over a wide temperature range. Samples with x  = 0.2 exhibit a temperature-stable permittivity of εr ≈ 600 (Δ ε' r / ε 'r, mid ≈ 10 % between -80°C and 300°C) along with small dielectric losses (tan δ < 0.02 between -55°C and 265°C) at 1 kHz. These attributes qualify these compositions as suitable high temperature capacitor dielectric materials. Graphical abstract: Image, graphical abstract